As decisões de investimento e a instabilidade financeira - Bueno, Roberta Nascimento [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Initially, the text handles the theories of ancient classical and changes with the emerging of the debates of the schools of economic of Keynes and Kalecki. Over the years, from 1930 onwards, investment theories were debated and modified by various schools of economic thought. One of the debates that stands out in this work are the theories of Minsky that will bring new reformulations to Keynesian theory and a greater focus on psychological factors as determinants of investment decisions. Through financial instability hypothesis Minsky explains how the decisions to invest and the access to credit cause instability to financial system. Finally the work will show how access to credit is material when companies decide to invest and how these investments are often handled due to information asymmetries in the market. The financial institutions seek to maximize their profits while dribbling moral hazard and adverse selection, and thus the government needs to intervene once in a while as a regulator to maintain the solvency of the system

Inicialmente o texto mostra as teorias dos antigos clássico e as alterações com o surgimento do debates das escolas econômicas de Keynes e Kalecki. Com o passar dos anos, de 1930 em diante, as teorias do investimento foram modificadas e debatidas por diversas escolas econômicas. Um dos debates que se salienta nesse trabalho são as teorias de Minsky que vão trazer novas reformulações para a teoria keynesiana e um maior enfoque nos fatores psicológicos como determinantes nas decisões de investimento. Através da hipótese de instabilidade financeira Minsky explica como as decisões de investir e o acesso ao crédito causam instabilidade no sistema financeiro. Finalmente o trabalho vai mostrar como o acesso ao crédito é essencial no momento em que as empresas decidem investir e como muitas vezes esses investimentos são abordados devido as assimetrias de informação do mercado. As instituições financeiras buscam maximizar seus lucros e ao mesmo tempo driblar o risco moral e a seleção adversa, e com isso o governo necessita intervir em alguns momentos como regulador para manter a solvência do sistema
Keywords: Economia; Economia - Estudo e ensino; Sociedades de credito e financiamento; Instituições financeiras; Financiamento; Empresas - Financiamento